Strategi Peningkatan Kualitas Bibit Cengkeh Melalui Inovasi Ukuran Benih Dan Media Tanam - Tuti Handayani Arifin; Zainuddin Basri; Maemunah Maemunah (Mitra Sains, 2020)
This study aimed to determine the effect of different seed sizes and planting media on the growth of clove seedlings. This research was conducted in the experimental station of the Faculty of Agriculture, Tadulako University from January to July 2019. This research was in the form of field trials and was designed with a split plot design with the main plot being the type of planting media consisting of 1) sawdust, 2) compost and 3) cocopeat. The subplots consist of large, medium, and small seeds. There were nine treatment combinations and each combination was repeated three times so that in total there were 27 experimental units. The results showed that there was an interaction effects between seed size and type of planting media. The best seed size treatment is found in large seed sizes. Sawdust media produces plant height, number of leaves aged 2,4,6 MST, stem diameter and wet weight of plants aged 8 MST higher than other planting media.